2015
DOI: 10.1177/0009922815584548
|View full text |Cite
|
Sign up to set email alerts
|

Suppurative Cervical Lymphadenitis in Infancy

Abstract: Incidence of MRSA is high in infants with cervical lymphadenitis who fail empirical antibiotic therapy and require surgical management. Empirical coverage for cervical lymphadenitis with β-lactam antibiotics may provide inadequate coverage for early infection in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…In a tertiary care setting such as our institution, children with suppurated cervical lymphadenitis are seen after first‐line antibiotic treatment usually performed at home so that, after admission, they are promptly submitted to ultrasonography, needle aspiration for both diagnosis and treatment, with ultrasonography guidance depending on the depth of the node involved, and intravenous second‐line antibiotic treatment is started. We were able to identify causative organism in 62% of cases, which is within the range reported in the literature (36%‐87%) . If there is suppuration recurrence, we perform more needle aspirations.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…In a tertiary care setting such as our institution, children with suppurated cervical lymphadenitis are seen after first‐line antibiotic treatment usually performed at home so that, after admission, they are promptly submitted to ultrasonography, needle aspiration for both diagnosis and treatment, with ultrasonography guidance depending on the depth of the node involved, and intravenous second‐line antibiotic treatment is started. We were able to identify causative organism in 62% of cases, which is within the range reported in the literature (36%‐87%) . If there is suppuration recurrence, we perform more needle aspirations.…”
Section: Discussionsupporting
confidence: 73%
“…We were able to identify causative organism in 62% of cases, which is within the range reported in the literature (36%-87%). 1,[4][5][6]9,10 If there is suppuration recurrence, we perform more needle aspirations. Following such a management protocol, in our group of 60 patients, there was a 98% probability of avoiding surgical drainage.…”
Section: Synopsis Of Key Findingsmentioning
confidence: 99%
“…6 In addition, 2 recent studies from the US about microbiologic trends in pediatric cervical infections found that the incidence of methicillin-resistant S. aureus had increased, especially in patients refractory to the initial regimen of empirical antibiotics. 15,16 However, identification of microorganisms in patients treated with long-term antibiotics would be problematic. In our study, causative organisms were detected only in 4 of 11 (36.4%) patients who received intravenous antibiotics for more than 3 days.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, fastidious or noncultivable organisms, namely, Clostridium butyricum ( 20 , 21 ), Finegoldia magna ( 22 , 23 ), and Fusobacterium nucleatum ( 24 , 25 ), were detected in necrotizing enterocolitis, urinary tract infection, and sepsis, respectively. Moreover, we identified Streptococcus pneumoniae ( 26 , 27 ) from septic arthritis, Acinetobacter baumannii ( 28 , 29 ) in ascites from a patient with perforated appendicitis, Streptococcus intermedius ( 30 , 31 ) from subdural empyema, and Staphylococcus aureus ( 32 34 ) from lymphadenitis. All specimens with true and possible pathogens (except one blood specimen from septic arthritis) were collected following antibiotic treatment.…”
Section: Discussionmentioning
confidence: 99%